Avaliação da susceptibilidade à corrosão galvânica em aços inoxidáveis ferrítico AISI 444 e austenítico AISI 304 utilizados na fabricação de reservatórios térmicos de aquecimento solar - Frederico Guilherme Dantas dos Santos (2005)
The solar energy industry in Brazil has been increasing at rates higher than those of other national industries. In the solar energy industry, the boiler or reservoir is made of AISI 304 stainless steel and is used to store water that is heated by a solar collector. The isolation used on the external surface of the boiler is poly (urethane) and aluminum. Themain body of the boiler is of AISI 444 stainless steel, which may be less expensive than AISI 304 steel, and which reduces the economic cost of the process. However, some parts of the equipment require a material with a higher workability than that of ferritic steel, and, for this reason, the parts are built with AISI 304 austenitic steel. The use of twodifferent materials in contact with each other can produce galvanic corrosion. The objective of this work was to study the corrosion resistance of the two different types of stainless steel, austenitic and ferritic, used in fabrication of water reservoirs in the solar energyindustry. Electrochemical potentiodynamic tests and immersion tests were used in the evaluation of the galvanic corrosion. The electrolyte used was a 3% sodium chloride solution and water. The galvanic potential obtained for the pair of polished steels was -91mV, and -70mV for the unpolished steels. The galvanic current density was 55 nA/cm2 for the steels with and without polishing. The superficial treatment influenced the corrosion resistance of the pair of steels. The unpolished AISI 304 steel was anodic in relation to the AISI 444 steel, and the polished AISI 304 steel was cathodic in relation to the polishedAISI 444 steel.